The Effectiveness of PAI Learning with Blended Learning Models at Private Islamic High Schools in Palangka Raya - Rohim, Abdur; Normuslim, Normuslim; Syabrina, Muhammad (Journal of Quality Assurance in Islamic Education (JQAIE), 2021)
This research is based on learning problems that cannot be carried out face-to-face because of the prolonged Covid-19 pandemic condition until now, so learning must be carried out by blended learning or face-to-face distance at private Islamic high schools throughout Palangka Raya to reduce the spread of the virus. Covid-19 continues to increase. For this reason, the formulation of the problem in this study is 1) How is the effectiveness of PAI learning with blended learning models in private Islamic high schools throughout Palangka Raya? 2) What are the teacher's obstacles in the PAI learning process with the blended learning model in private Islamic high schools throughout Palangka Raya? This study aims to describe the effectiveness of PAI learning with the blended learning model and the teacher's obstacles in the learning process at private Islamic high schools throughout Palangka Raya. This research was conducted using the descriptive qualitative method. This research was conducted at SMA Muhammadiyah 1 Palangka Raya, SMA Muhammadiyah 2 Palangka Raya and SMA Nahdatul Ulama Palangka Raya. The subjects of this research are teachers who teach PAI subjects. For data collection using observation techniques, interviews, and documentation. The data validation technique uses persistence and constancy of observation and triangulation. Meanwhile, data analysis was carried out using data collection, data reduction, data display, and conclusion drawing/verification. The results of this study indicate that: 1) The effectiveness of PAI learning with the blended learning model in private Islamic high schools throughout Palangka Raya is still not maximized because students' interest and motivation to learn decreases and students feel bored with the distance learning model or blended learning so that the strategy used by the teacher in teaching can not run optimally. In addition, the small allocation of learning time also causes the explanation of the material to be less effective. 2) The teacher's obstacle in the learning process is the lack of student participation in learning. This is because the main obstacles that occur are the difficulty of the signal and the weak internet network that occurs to students. In addition, the limited quota is also an obstacle for students who have economic limitations.